Contribution of patient registries to regulatory decision making on rare diseases medicinal products in Europe - Carla J. Jonker; Carla J. Jonker; Elisabeth Bakker; Elisabeth Bakker; Xavier Kurz; Kelly Plueschke (Frontiers in Pharmacology, 2022)
Between 2000 and 2021, the European Medicines Agency (EMA) assigned the orphan designation to over 1,900 medicines. Due to their small target populations, leading to challenges regarding clinical trial recruitment, study design and little knowledge on the natural history of the disease, the overall clinical evidence submitted at the time of marketing authorisation application for these medicines is often limited. Patient registries have been recognised as important sources of data on healthcare practices, drug utilisation and clinical outcomes. They may help address these challenges by providing information on epidemiology, standards of care and treatment patterns of rare diseases. In this review, we illustrate the utility of patient registries across the different stages of development of medicinal products, including orphans, to provide evidence in the context of clinical studies and to generate post-authorisation long term data on their effectiveness and safety profiles. We present important initiatives leveraging the role of registries for orphan medicinal products’ development and monitoring to ultimately improve patients’ lives.